Exploring the Applicability of Robot-Assisted UV Disinfection in Radiology - McGinn, Conor; Scott, Robert; Donnelly, Niamh; Roberts, Kim L.; Bogue, Marina; Kiernan, Christine; Beckett, Michael (Frontiers in Robotics and AI, 2021)
The importance of infection control procedures in hospital radiology departments has become increasingly apparent in recent months as the impact of COVID-19 has spread across the world. Existing disinfectant procedures that rely on the manual application of chemical-based disinfectants are time-consuming, resource-intensive and prone to high degrees of human error. Alternative non-touch disinfection methods, such as Ultraviolet Germicidal Irradiation (UVGI), have the potential to overcome many of the limitations of existing approaches while significantly improving workflow and equipment utilization. The aim of this research was to investigate the germicidal effectiveness and the practical feasibility of using a robotic UVGI device for disinfecting surfaces in a radiology setting. We present the design of a robotic UVGI platform that can be deployed alongside human workers and \hl{can operate autonomously within cramped rooms, thereby addressing two important requirements necessary for integrating the technology within radiology settings}. In one hospital, we conducted experiments in a CT and X-ray room. In a second hospital, we investigated the germicidal performance of the robot when deployed to disinfect a CT room in less than 15 minutes, a period which is estimated to be 2 to 4 times faster than current practice for disinfecting rooms after infectious (or potentially) infectious patients. Findings from both test sites show that UVGI successfully inactivated all of the measurable microbial load on 22 out of 24 surfaces. On the remaining two surfaces, UVGI reduced the microbial load by 84% and 95% respectively. The study also exposes some of the challenges of manually disinfecting radiology suites, revealing high concentrations of microbial load in hard-to-reach places. Our findings provide compelling evidence that UVGI can effectively inactivate microbes on commonly touched surfaces in radiology suites, even if they were only exposed to relatively short bursts of irradiation. \hl{Despite the short irradiation period, we demonstrated the ability to inactivate microbes with more complex cell structures and requiring higher UV inactivation energies than SARS-CoV-2, thus indicating a high likelihood of effectiveness against coronavirus.